Rare-earth permanent magnet in magnetic system of electron accelerator with the energy of 10 MеV - Bovda, V.A.; Bovda, A.M.; Guk, I.S.; Kandybey, S.S.; Kononenko, S.G.; Lyashchenko, V.N.; Mytsykov, A.O.; Onischenko, L.V. (Вопросы атомной науки и техники, 2019)
The radiation resistance of Sm-Co and Nd-Fe-B magnets under 10 MeV electron beam was studied. The simulation and design of a magnetic system for electron beam analysis of a technological accelerator for energy up to 10 MeV was carried out. The key component of magnetic system was Sm₂Co₁₇ magnets with the size of 30х24х12 mm. The maximum magnetic field in the magnetic system was 0.3 T.